Amelioration of particulate matter-induced oxidative damage by vitamin c and quercetin in human bronchial epithelial cells. (February 2016) - Jin, Xiaoting; Su, Ruijun; Li, Ruijin; Song, Li; Chen, Meilan; Cheng, Long; Li, Zhuoyu
Abstract: Exposure to fine particulate matter (PM2.5 ) has a close association with respiratory damage. Vitamin c and quercetin have been documented to possess antioxidant and anti-inflammation properties. However, their potential protective effects against PM2.5 -induced respiratory damage have not been evaluated yet. Hence, the study was aimed to investigate their protective effects and delineate the possible mechanisms. The results indicated that PM2.5 depleted the cell viability of 16HBE cells, elevated reactive oxygen species (ROS) generation, and inhibited mitochondrial genes expressions, including fusion proteins Mfn1 and OPA1, along with biogenesis markers SIRT1 and p53R2 . Additionally, the damage of mitochondrial morphology was observed upon PM2.5 exposure using both JC-1 and MitoTracker Red staining. Expressions of mitochondrial respiratory chain genes including NDUFS2 and UQCRI1 were also attenuated by PM2.5 exposure. Furthermore, PM2.5 promoted the mRNA levels of NADPH oxidase and inflammation cytokines. However, the addition of vitamin c or quercetin strikingly antagonized the PM2.5 -induced toxic effects. Collectively, these findings suggest that vitamin c and quercetin have repressive roles in respiratory oxidative damage incurred by PM2.5, which provide the theoretical basis about intervention and control of food nutrients on PM2.5 -induced human adverse health. Highlights: Vitamin c and quercetin can relief the toxicity caused by PM2.5 on 16HBE cells. Vitamin c and quercetin prominently alleviate the PM2.5 -induced ROS generation. Vitamin c and quercetin supplement significantly counteract the NOX2 and p67 phox expressions incurred by PM2.5 . Vitamin c and quercetin have suppressive roles in mitochondrial structure and function damaged by PM2.5 . Vitamin c and quercetin play protective effects on inflammation response affected by PM2.5 .